Analisis tentang Tindak Pidana Perdagangan Orang (Human Trafficking) dalam Perspektif Kriminologi - Muhammad Jarnawansyah (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
Human Trafficking is a crime in the form of human transaction. In Indonesia order to ensnare perpetrators of human trafficking, we use Law Number 21 of 2007 concerning the Eradication of Criminal Acts of Human Trafficking. The purpose of this study is to determine and analyze the factors that cause human trafficking, the consequences of human trafficking crimes and how to overcome human trafficking crimes in the perspective of criminology, the negative impacts of human trafficking on the social environment. This study uses a normative legal research method, the data used is primary data. The analysis technique used is a qualitative approach. The results of this study are that human trafficking crimes seen from a criminological perspective can be associated with many things, including lack of awareness of poverty, low education, the desire to get rich quick, cultural factors, law enforcement. Human trafficking prevention can be classified into two types. Preventive prevention efforts are all efforts to reduce the space for movement and opportunities for crimes to be committed, and repressive prevention efforts are actions taken by law enforcement officers after a crime or criminal act has occurred. In eradicating and reducing trafficking, cross- country cooperation is also needed.